Curcumin induces apoptosis in trophoblast model cell line (Medical Journal of Indonesia, 2018)
Background: Several studies have reported that curcumin exerts chemopreventive effects in various type of cancers, through several mechanisms, however, the effect of curcumin on carcinogenesis in patients with hydatidiform mole has not yet been investigated. This study was conducted to evaluate the effect of curcumin on apoptosis, proliferation, and nuclear translocation of endothelial nitricoxide synthase in trophoblast cells induced by estradiol in complete hydatidiform mole (CHM). Methods: In this in vitro study, trophoblast cells were divided into six groups, the control group (trophoblast cells were exposed to 100 pg/mL of 17-β estradiol) and the treatment group (trophoblast cells were exposed to 100 pg/mL of 17-β estradiol in the presence of curcumin with doses: 50, 100, 200, 400, and 800 μM). At the end of study, the cell proliferation was analyzed using MTT assay and apoptosis with TUNEL test in each group thropoblast cell. eNOS translocation was assayed using confocal laser scanning microscopy at the various dose of curcumin. Results: Curcumin at the doses of 200, 400, and 800 μM significantly decreased the proliferation and increased the apoptotic index in curcumin-treated group compared to those in the control group (p<0.05). All doses of curcumin treatment significantly decreased the nuclear eNOS expression compared to that in the control group. The three highest doses of curcumin increased cytoplasmic eNOS expression compared to that in control group.Conclusion: Curcumin inhibits the proliferation and modulates the apoptosis of trophoblast cells induced by estradiol in CHM involvement.